Operative Intercostal Chest Drain Is Not Required following Extrapleural or Transpleural Esophageal Atresia Repair - Paramalingam, Saravanakumar; Burge, David M.; Stanton, Michael P. (European Journal of Pediatric Surgery, 2013)
Background Approximately half of the United Kingdom patients undergoing esophageal atresia (OA) repair have an operative intercostal chest drain (ICD) placed (2008 British Association of Pediatric Surgeons Congenital Anomalies Surveillance Study data). We reviewed our experience of OA repairs to evaluate if an ICD placement is necessary.Methods Patients with OA/distal tracheoesophageal fistula (TOF), treated between January 1990 and January 2010, were identified by retrospective review of a prospectively maintained electronic database and patient case notes.Main Results A total of 112 consecutive patients were identified, of whom 107 were included (73 male). Five were excluded as no case notes were available. Median birth weight was 2,597 g (range 924 to 4,245 g) and median gestational age was 38 weeks (27 to 41 weeks). Median age at discharge was 22 days (3 to 440 days) and median follow-up was 3.5 years (0 to 18 years). Patients were analyzed in two groups—group 1 (n = 73) had an extrapleural (EP) repair, of which 23 had a pleural breach and group 2 (n = 34) had a purposeful transpleural (TP) approach (surgeon preference). Eleven patients (10%) had an operative ICD, of which six patients were in group 1 and five in group 2. These 11 patients had an uncomplicated postoperative course and all operative ICD were removed within 48 hours of surgery. Of the 96 patients that did not have an operative ICD, only 2 (2%) required postoperative intervention. One patient, in group 2, had a postoperative ICD inserted for a simple pneumothorax at 12 hours and removed at 48 hours. The other patient, in group 1, had a clinically detected anastomotic leak after 48 hours and required operative repair.Conclusion An operative ICD is not required following OA/distal TOF repair, whether the approach is EP or TP. ICD that were electively placed (in 10%) served no clinical purpose.
Keywords: esophageal atresia; intercostal chest drain; extrapleural